Government organisation and economic development : papers and proceedings of the fourth Study Conference on Problems of Economic Development, Paris, 7th-11th September 1964 - Moodie, Graeme C.; Organisation for Economic Co-operation and Development (Paris ; [London : O.E.C.D. ; H.M.S.O., 1966)
This volume comprise of papers and proceedings of the fourth Study Conference on Problems of Economic Development, Paris, 7th-11th September 1964.
lje 19/10/18
Loans
Keywords: Economic policy; Economic development